2023
DOI: 10.1186/s12888-023-05121-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Heterogeneity in perinatal depression: a comprehensive review

Ahmed Waqas,
Mahnoor Nadeem,
Atif Rahman

Abstract: Perinatal depression (PND) is a significant contributor to maternal morbidity globally. Recognized as a major cause of poor infant development, epidemiological and interventional research on it has increased over the last decade. Recently, studies have pointed out that PND is a heterogeneous condition, with variability in its phenotypes, rather than a homogenous latent entity and a concrete diagnosis, as previously conceptualized in psychometric literature and diagnostic systems. Therefore, it is pertinent tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 106 publications
1
7
0
Order By: Relevance
“…Confirmation of the findings described in our earlier work [30] was found in review papers published in the past 4 years ([9,34 ▪ ,72,73 ▪▪ ,74 ▪▪ ,75–80,81 ▪ ]. Alteration or disruption in the parent-infant relationship has been mentioned in several reviews, including a review on effects of perinatal interventions on parent anxiety, infant socio-emotional development and parent-infant relation outcomes [82].…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...supporting
confidence: 70%
See 1 more Smart Citation
“…Confirmation of the findings described in our earlier work [30] was found in review papers published in the past 4 years ([9,34 ▪ ,72,73 ▪▪ ,74 ▪▪ ,75–80,81 ▪ ]. Alteration or disruption in the parent-infant relationship has been mentioned in several reviews, including a review on effects of perinatal interventions on parent anxiety, infant socio-emotional development and parent-infant relation outcomes [82].…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...supporting
confidence: 70%
“…Some studies examine differential offspring neurobehavioral developmental outcomes in groups of women showing different trajectories of onset, intensity and chronicity of depression symptoms, using cutting-edge statistical methods and machine learning algorithms [74 ▪▪ ]. These provide evidence that offspring of mothers with for example, a trajectory of chronic high depression (stable from pregnancy to postpartum) have more conduct, emotional, social (e.g., poor peer relations) problems, externalizing and/or internalizing problems, depression and emotional dysregulation.…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...mentioning
confidence: 99%
“… 6 , 7 In fact, suicidal ideation is part of the typical screening for PND. 8 Emerging evidence 9 suggests that those with PND are a heterogenous group. For instance, antenatal (during pregnancy) and postnatal (maximally within 1 year after delivery) depression may have different causes and symptom clusters.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, antenatal (during pregnancy) and postnatal (maximally within 1 year after delivery) depression may have different causes and symptom clusters. 9 Existing literature 10 , 11 , 12 suggests that suicidal ideation is common among women with antenatal depression, while data on risk of suicidal behavior, including attempted and completed suicide, are lacking. Studies 13 , 14 have shown that 3% to 19% of women with postnatal depression endorsed suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…While depression is prevalent across the lifespan for both sexes globally [2], the World Health Organization (WHO), International Monetary Fund (IMF) and other international organizations emphasize the significance of maternal depressive disorders as an issue of global population health as they are well known to contribute to infant and child morbidity [3][4][5]. Poor outcomes for children may include lower birth weight, suboptimal infant growth, decreased breastfeeding rates, developmental delay, behavioral problems, compromised executive functions and other short-and long-term physical and mental health problems [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%